Maternal methylmercury exposure during early-life periods adversely affects mature enamel structure of offspring rats at human exposure levels: a concern for oral health - Chemelo, Victória Santos; Bittencourt, Leonardo Oliveira; Nascimento, Priscila Cunha; Paiva, Mayra Frasson; Delbem, Alberto Carlos Botazzo; Pessan, Juliano Pelim; do Espírito Santo, Alexandre Ribeiro; Albuquerque, Alan Rodrigo Leal; Angélica, Rômulo Simões; Crespo-Lopez, Maria Elena; Pessanha, Sofia; Aschner, Michael; et al. (Frontiers in Public Health, 2023)
Although there are many studies on the health effects of methylmercury (MeHg) toxicity during in utero and early development, little is known about its effects on mineralized tissues present in the oral cavity, such as enamel structure. Therefore, this study evaluated the effects of MeHg exposure on the physico-chemical, ultrastructural and functional properties of mature tooth enamel. Specifically, we studied offspring of mothers exposed to MeHg during the prenatal and postnatal periods which are the developmental stages associated with tooth enamel formation. Female rats were exposed to MeHg at a dose of 40 μg/kg/day for 42 days of pregnancy and lactation. The enamel of offspring was analyzed by (1) Fourier Transform Infrared Spectroscopy and Raman to assess physicochemical composition, (2) Scanning Electron Microscopy for ultrastructural evaluation, (3) Transmitted Polarizing Light Microscopy for analysis of the enamel extracellular matrix, and (4) resistance and hardness were evaluated by microhardness. The results showed that MeHg exposure during this sensitive enamel formation period induced changes in inorganic and organic content and enamel prisms ultrastructure alterations by disturbing molecular order of secretory enamel organic extracellular matrix due to a decreased enamel strength. These novel findings establish for the first time that maternal exposure to MeHg pre and postnatal promoted relevant changes in mature enamel of their offspring rats.